Portraying the Use of Artificial Intelligence Toward the Quality of the EFL Students’ Writing Tasks - Zumrotul Fauziah; Aszahari Nova Nur Sa'idatul Nisa' (IKIP PGRI Bojonegoro, 2026)
Artificial Intelligence (AI) is a new technology that can help people answer questions, provide directions, and perform various tasks based on their commands. The technology can be a helpful tool, but it is also harmful. In education, especially in higher education, students can easily find answers to quizzes, write papers, locate types of literature, and create presentations in just a second by using artificial intelligence. Hence, this study aimed to describe the use of artificial intelligence among university students and to analyze the quality of students’ writing tasks from the perspectives of both students and lecturers. This study uses a quantitative descriptive method. The data is collected through questionnaires. There are two kinds of questionnaires. The first is for students; the questionnaires aim to gather information on the types of artificial intelligence university students use to complete their writing tasks. The second is for the lecturers; the questionnaires aim to gather their perceptions of the quality of tasks completed by students using AI. The questionnaires are shared through Google Forms. The population of this research consists of fourth-semester students in the Islamic Education study program. The sample consists of 40 students, selected using simple random sampling. However, only 38 students responded to the questionnaire. The results show that 52% of fourth-semester students use AI to complete their tasks. Most students (37%) used ChatGPT to complete their tasks. The students perceive that they use AI only to find ideas or inspiration, but they still read the references to complete the tasks. They realize that the use of AI can decrease their analytical competence. However, they perceive AI as helpful to them. The lecturers perceive that the use of AI can help students complete tasks. However, it can decrease the students' creativity, critical thinking, and analytical competence. Further, the use of AI can increase plagiarism, as most students copy and paste from AI websites. Therefore, the lecturers suggest that student